NAVIGATING THE DIGITAL MARKETPLACE: THE ROLE OF AI TRANSPARENCY IN BUILDING CONSUMER TRUST IN E-COMMERCE - Vijaya Kumar Reddy Atla, (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2024)
Artificial intelligence's incorporation into e-commerce platforms has completely changed online retail and how customers engage with online marketplaces. Although AI technologies provide previously unheard-of levels of personalization and operational efficiency, consumer trust is seriously threatened by their complexity and frequently opaque decision-making processes. This article explores how transparent methods boost user trust and promote long-term business growth by examining the crucial relationship between AI openness and consumer confidence in e-commerce contexts. The article shows how businesses can successfully balance technological innovation and consumer trust-building strategies, thereby promoting long-term success in the digital marketplace, by thoroughly analyzing transparency levels, implementation difficulties, and trust models.